Analisis Implementasi Relaksasi Pajak Bumi dan Bangunan Perdesaan dan Perkotaan di Kota Bandung pada Masa Pandem COVID-19 - Andina Tri Dewanti; Yeti Apriliawati; Riauli Susilawaty Hutapea (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
During the Covid-19 pandemic, policies are needed that can mediate the issue of government financial needs in providing services to the community, but at the same time do not burden the community. This study aims to find out how the implementation of the policy for the relaxation of the Land and Building Tax in Rural and Urban in Bandung (PBB-P2) during the Covid-19 pandemic. This research was conducted at the Regional Revenue Agency of Bandung City. The research method is descriptive qualitative with data collection is carried out by interview and documentation study. The data analysis technique used is the Miles and Huberman model analysis technique. The results of this study indicate the implementation of the relaxation of PBB-P2 in Bandung City has been carried out well, however, it is necessary to improve the communication aspect, and human resources aspect. The function of this policy has helped the need for government revenues while helping to ease the burden on taxpayers, but still should be carefully designed so that tax collection remains efficient.